Extraction and Stability of Natural Dyes From The skin of Red Dragon Fruit - Ni Putu Bella Trisna Dewi; Ni Made Ayu Suardani Singapurwa; I Gede Pasek Mangku (SEAS (Sustainable Environment Agricultural Science), 2020)
Dragon fruit skin contains anthocyanin dyes which are quite high. Anthocyanins are dyes that give red color and can be used as natural dyes for food. This study aims to determine the ratio of the 10% citric acid solution with the time of maceration to obtain the highest anthocyanin levels and to determine the stability of the red dragon fruit peel extract. The research design used was a factorial completely randomized design (CRD) with two factors, namely the ratio of red dragon fruit peel pulp with 10% citric acid solvent consisting of three levels: 1: 3; 1: 6; 1: 9. The second factor is the length of maceration of the red dragon fruit skin which consists of three levels: 3 days; 3.5 days; 4 days. Analysis of red dragon fruit peel extract includes: yield, anthocyanin levels, pH value, color intensity, and stability test. The best treatment of red dragon fruit peel extraction was obtained in the sample ratio of 10% citric acid solution (1: 3) and the duration of maceration for 4 days with a yield of 22.92%; pH value of 1.84; anthocyanin levels of 52.27 mg / L; L * color intensity of 16.54; color intensity a * of 75.57; color intensity b * was 9.63 and the best anthocyanin dye stability test was obtained at a pH of 3 and a temperature of 7 Â° C.